Las actividades económicas de la provincia de Costa Rica. 1569-1610 - Quirós, Claudia (1987)
Studies the economic activities carried out in the Province of Costa Rica be the conqueror- settler- “encomenderos”. Marketing of tribute in kind and livestock were the basis of the Colonial economy during the period under analyses (1569-1610).